Watermelon Genotypes and Weed Response to Chicken Manure and Molasses-Induced Anaerobic Soil Disinfestation in High Tunnels - Muhammad Sohaib Chattha; Brian K. Ward; Chandrasekar S. Kousik; Amnon Levi; Bhupinder S. Farmaha; Michael W. Marshall; William C. Bridges; Matthew A. Cutulle (Agronomy)
Weed and disease management in organic watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai] production is challenging. Yellow nutsedge (Cyperus esculentus L.) and Palmer amaranth (Amaranthus palmeri S. Wats.) are two competitor weeds in watermelon plasticulture production systems. Anaerobic soil disinfestation (ASD) is an emerging non-chemical approach to control weeds and soilborne plant pathogens, especially in organic farming. The effect of ASD treatments on weeds and soilborne diseases is being documented on different specialty crops. However, the impact of ASD treatments on the crop and crop genotypes; specifically watermelon has not been elucidated. Therefore, the impact of chicken manure and molasses (CMM)-induced ASD on twenty commercially available watermelon genotypes/rootstocks and major weed species was evaluated in a high tunnel experiment. The experiment was constructed as a randomized complete block design with three replications. The treatments consisted of a factorial of carbon source (1) non-treated check (CK), (2) CMM by twenty watermelon genotypes and rootstock. Soil treated with carbon CMM demonstrated significantly greater cumulative anaerobicity (246,963) activity relative to CK (575,372). Under anaerobic conditions, CMM achieved 91% weed control compared to CK. A lower number of yellow nutsedge (2) and Palmer amaranth (1) counts were recorded in CMM compared to CK (8) and (28), respectively. Among watermelon genotypes, ‘Extazy’, ‘Powerhouse’, ‘Sangria’, and ‘Exclamation’ had greater vigor 8.5, 8.4, 8.4, and 8.3, respectively, at 28 days after transplanting in CMM-treated soil. Greater watermelon plant fresh biomass was recorded in CMM-treated soil for ‘Extazy’ (434 g), ‘Powerhouse’ (409 g), ‘Exclamation’ (364 g), and ‘Sangria’ (360 g). This study demonstrated the variable response of watermelon genotypes to CMM-induced ASD and provides a guide for germplasm selection in organic watermelon production under field conditions.